Encouraging Healthy Body-Image: Are Parents Sending Effective Messages to Children? - (:unkn) unknown (My University, 2013)
This investigation tested and applied Bogenschneider (1996) Ecological Risk and Protective Theory to the process of body-image development. In order to understand what is considered risk and protective behaviors, qualitative directed content analysis was used to analyze the health experts' opinion. Twenty-three online brochures were analyzed, resulting in two protective themes (parents as educators and parents providing an appropriate environment) and two risk themes (negative role model behaviors and negative complimenting behaviors). From the themes, items were created and quantitative data was collected using paper/pencil surveys. Data collection resulted in 126 parent and 126 child responses. Results provide support for the Ecological Risk and Protective Theory. First, data show many ecological variables influence body-image development on cognitive, affective, and behavioral levels, including parental complimenting behavior, media and parental influence. Second, results support Bogenschneider's (1996) argument that risk and protective processes are not dichotomous; rather work together in health development. Specifically, findings show even though mothers implement protective behaviors, the risk behaviors employed by parents and the media counteract the preventive measures. Important practical implications emerge from the data as well. Data demonstrated children are not resilient enough to overcome risky media messages and images, as media was found to impact body-image negatively on cognitive, affective, and behavioral levels. Thus, it is recommended parents need to spend greater time educating children about media literacy. In addition, results revealed mothers and fathers relayed gender-relevant messages to same-sex children. In terms of risk behaviors, mothers and fathers perpetuated societal stereotypical body norms to sons and daughters. Theoretical and practical implications and avenues for future research are presented.
Keywords: Body-Image; Communication; Ecological Risk and Protective Theory; Influence; Parental Communication